Islamic Community Empowerment Through Social Media In Tanjungbalai City - Aidil Anwar; Muniruddin Muniruddin (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
The purpose of this study is to see how the development of Islamic community empowerment is linked through social media. The link between community empowerment and social media can be seen from the influence of social media which is quite complex in empowering the community, due to the rapid development of the media, everything can be known through the media. Because of that, many people use it in all ways, including empowering their lives to be more worthy and also upgrading skills and knowledge through social media. The research method used in this research is descriptive qualitative research. The data collection technique used in this research is to use library research, namely by collecting data through journals, scientific articles and other literature related to community empowerment. In empowering the community itself, social media plays a role in education, information, information and also as a social liaison between the community and the government as well as other communities. The media also functioned as a vessel in obtaining various knowledge in the form of values, prevailing norms. The media plays a role in empowering by becoming an intermediary in conveying information to the public. So far, the media can help increase the success of the empowerment process and support community capacity building practices. In the context of empowering the Islamic community, the majority of people who are Muslim in Tanjungbalai City with a ratio of 3:4 of the total population make the Islamic community in Tanjungbalai the right object of empowerment. Moreover, as a religion that is the majority, it would be better if it is able to show the quality to become a superior society.